Ansietas, ibu hamil, terapi peng PENURUNAN ANSIETAS IBU DALAM MENJALANI KEHAMILAN SAAT PANDEMI COVID 19 MELALUI TERAPI PENGHENTIAN PIKIRAN DI KELURAHAN CIPINANG BESAR UTARA, JAKARTA TIMUR: PENURUNAN ANSIETAS IBU DALAM MENJALANI KEHAMILAN SAAT PANDEMI COVID 19 MELALUI TERAPI PENGHENTIAN PIKIRAN DI KELURAHAN CIPINANG BESAR UTARA, JAKARTA TIMUR - Sri Laela; Ening Wahyuni (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2021)
Mothers who experience pregnancy during the Covid 19 pandemic are at risk of experiencing anxiety, its because pregnant women feel anxious, worried about being exposed to the virus which can affect their health and afraid that later they have to give birth without the support of their closest people / family members, due to restrictions according to the health protocol that is implemented in the hospital. The purpose of this study was to identify the effect of thought stopping therapy on maternal anxiety during pregnancy during the COVID-19 pandemic. The research method used was a quasi-experimental one group with pre-test - post-test design with consecutive sampling method. The sample used was 20 pregnant women. This study used the Zung Self - rating Anxiety Scale (ZSAS) questionnaire. The characteristics of mothers who pregnancy during the Covid 19 pandemic experienced moderate to severe anxiety. The results showed that there was a significant reduction in anxiety (p-value = 0.000) after receive Ners nursing action and thought stopping therapy. Nursing actions and thought stopping therapy can reduce maternal anxiety during pregnancy during the Covid 19 pandemic.